Promoting Religious Tolerance through Kampung Moderasi Beragama: A Study of the Implementation of Kepdirjen Bimas Islam No. 137/2023 in West Java - Kustana, Kustana; Muhlas, Muhlas (TEMALI : Jurnal Pembangunan Sosial, 2025)
This study aims to explain the implementation of the Keputusan Direktur Jenderal Bimbingan Masyarakat Islam (Kepdirjen Bimas Islam) Number 137 of 2023 regarding the establishment of Kampung Moderasi to prevent religious conflict polarization. The research examines several Kampung Moderasi cases in West Java, particularly in the cities of Bandung and Tasikmalaya, which have implemented this policy. Kampung Moderasi aims to create a harmonious and tolerant environment in society by promoting the values of religious moderation. Using a qualitative approach, this study employs interviews, direct observation, and document review methods. The findings show that Bandung, Kampung Moderasi in Cibadak, Babakan Ciparay, and Sukawarna have made significant initiatives in strengthening interfaith relations through interfaith dialogue, educational programs, and social activities. Meanwhile, in Tasikmalaya, Kampung Moderasi in Nagarawangi and Empangsari have also made similar efforts to strengthen social cohesion and prevent conflict by developing inclusive, religion-based communities. However, despite the positive outcomes of this policy's implementation, several challenges remain, such as limited resources and the lack of participation from some segments of society. This study concludes that Kepdirjen Bimas Islam Number 137 of 2023 is effective in preventing religious conflict polarization, but there needs to be greater support from local governments, religious institutions, and society to enhance participation and ensure the sustainability of the program. The future implementation of this policy requires strengthened cooperation among stakeholders and more intensive monitoring.